PENGARUH RASIO FINANCIAL LEVERAGE DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR MANUFAKTUR PERIODE 2019-2021 - Ria Fitria Andriani; Lia Agatha (BALANCING: Accountancy Journal, 2023)
This thesis discusses the effect of financial leverage and liquidity ratios on company profitability. This type of research is quantitative research with hypothesis testing. The research sample is the financial statements of 30 manufacturing sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The source of research data is secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The data analyzed are profitability (variable Y) using Return On Asset (ROA) analysis, financial leverage variable (variable X1) using Debt to Asset Ratio (DAR) analysis, and liquidity variable (variable X2) using Current Ratio (CR) analysis. The results of the research that tested the hypothesis obtained data: (1) The financial leverage ratio (DAR) has a negative and significant effect on the profitability (ROA) of manufacturing sector companies on the Indonesia Stock Exchange for the period 2019-2021; (2) The liquidity ratio (CR) has a positive and significant effect on the profitability (ROA) of manufacturing sector companies on the Indonesia Stock Exchange for the period 2019-2021; (3) The ratio of financial leverage (DAR) and liquidity (CR) simultaneously has a positive and significant effect on the profitability (ROA) of manufacturing sector companies on the Indonesia Stock Exchange for the period 2019-2021.